2015
DOI: 10.1021/acs.jpclett.5b01508
|View full text |Cite
|
Sign up to set email alerts
|

Non-Band-Gap Photoexcitation of Hydroxylated TiO2

Abstract: The photochemistry of TiO2 has been studied intensively since it was discovered that TiO2 can act as a photocatalyst. Nevertheless, it has proven difficult to establish the detailed charge-transfer processes involved, partly because the excited states involved are difficult to study. Here we present evidence of the existence of hydroxyl-induced excited states in the conduction band region. Using two-photon photoemission, we show that stepwise photoexcitation from filled band gap states lying 0.8 eV below the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…Measurements employed an instrument (base pressure *4 9 10 -10 mbar) and laser system described elsewhere [41]. 2PPE (hm = 3.10-3.54 eV, 400-350 nm, 0.3-0.5 mW, spot diameter *0.5 mm) and UPS (He-I, hm = 21.2 eV, 58 nm and He-II, hm = 40.8 eV, 30 nm) spectra were recorded using a pass energy of 10 eV.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements employed an instrument (base pressure *4 9 10 -10 mbar) and laser system described elsewhere [41]. 2PPE (hm = 3.10-3.54 eV, 400-350 nm, 0.3-0.5 mW, spot diameter *0.5 mm) and UPS (He-I, hm = 21.2 eV, 58 nm and He-II, hm = 40.8 eV, 30 nm) spectra were recorded using a pass energy of 10 eV.…”
Section: Methodsmentioning
confidence: 99%
“… 28 30 At reduced and hydroxylated TiO 2 (110) surfaces, 2PPE spectra are dominated by a t 2 g → t 2 g excitation feature where the excited state lies ∼2.6–2.8 eV above E F . 28 , 30 32 The oscillator strength of this excitation is strongly dependent on the orientation of the electric field vector. This increases when the scattering plane is perpendicular to the [001] crystal azimuth, ( p- [001]).…”
mentioning
confidence: 99%
“…This increases when the scattering plane is perpendicular to the [001] crystal azimuth, ( p- [001]). 28 30 , 32 In contrast, a weaker feature is observed when the scattering plane is parallel to the [001] azimuth, ( s- [001]). 29 , 30 Furthermore, it has been shown that water and methanol adsorption influences this channel, altering the orbital character and resulting in an enhancement of the t 2 g → t 2 g excitation oscillator strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned difficulties to predict and utilize energy level alignment at semiconductor surfaces have proven to be particularly tedious for metal oxides such as ZnO or TiO 2 [24,25,26,27]. While one of the most promising wide band gap semiconductors for optoelectronic applications [28], ZnO surfaces are notoriously difficult to prepare and characterize, both experimentally and theoretically [29,30,31,32,33,34,35,36,37].…”
Section: Surface Electronic Structure Of Znomentioning
confidence: 99%